A Hobbesian qualm with space settlement. (June 2019) - Tachibana, Koji
Highlights: Protective, sustainable housing facilities for space settlement will be isolated and confined (i-c) accommodations. Long-duration sojourns in i-c environments can cause behavioral health deterioration and sociomoral performance degradation. Behavioral health deterioration and sociomoral performance degradation will become serious problems in future space settlements. Abstract: Imagining a new life in space is exciting. However, we should not overlook that psychological and interpersonal stressors due to isolation and confinement can cause crew members to experience behavioral health deterioration and sociomoral performance degradation. In the era of space settlement, such conditions will last throughout settlers' lives as facilities must be highly airtight to protect them against the hostile environment of space. Settlers' behavioral health and sociomoral performance will gradually decline, and the situation will only become progressively worse because no one on Earth will be able to intervene. The settlers might ultimately find themselves in a disastrous Hobbesian state of "war of all against all". Humans have yet to experience a comparatively long-duration sojourn in space and its consequences, so when considering possible scenarios in future space settlement, we must examine behavioral health problems due to the lifelong residence in isolated and confined facilities.